Prevalence of depression in COPD: A systematic review and meta-analysis of controlled studies. (August 2016) - Matte, Darlan L.; Pizzichini, Marcia M.M.; Hoepers, Andrea T.C.; Diaz, Alexandre P.; Karloh, Manuela; Dias, Mirella; Pizzichini, Emilio
Abstract: Background: Depression is frequently reported in association with COPD. However, the prevalence of depression in these patients ranges largely. This study aimed to systematically review the prevalence of depression in COPD and controls and to explore remaining causes of inter-study variability in the reported prevalence. Methods: A systemic review of the literature and a meta-analysis was performed to evaluate the source of variability in the reported rates of depression in stable COPD. Main eligibility criteria were: controlled studies with a sample size >100, outpatients with COPD diagnosed by spirometry and, use of a validated depression screening instrument. Results: From 1613 studies identified, eight controlled studies were included in the review. The number of participants in the pooled studies was of 5.552 COPD subjects and 5.211 controls. Using stricter criteria for study selection reduced the variability of the depression prevalence in COPD and controls, which was 27.1% [25.9–28.3] in COPD subjects and 10.0% [9.2–10.8] in the control group. The pooled odds ratio and 95% CI was 3.74 [2.4–5.9]. However, the heterogeneity across studies was high. Possible explanatory factor included sample sizes, COPD/controls ratio, smoker's/nonsmokers ratio and qualitative differences (source of subjects, instruments to screen depression, COPD severity, smoking status, and comorbidities). Conclusion: The study highlights the variability in estimates of depression prevalence in COPD. It could be explained by methodological differences across the included studies. This suggests that a standardization is critical to improve precision of the estimates. Highlights: The causes of variability in the prevalence of depression in COPD were investigated. The variability is consequence of methodological differences across studies. There is a need for establishing evidence-based recommendations for this studies. This would improve estimates precision and allow future comparisons between studies.